Features of the development of stress-related disorders with concomitant sleep disturbances due to military events - Kohut, Анна (Psychosomatic Medicine and General Practice, 2024)
The aim of this study was to assess the features of the development of stress-related with concomitant sleep disorders as a result of military events, by comparing the indicators in groups according to the level of manifestation of post-traumatic symptoms and determining the relationships according to the indicators of the results of diagnostic scales. The study data included Ukrainian-language: demographic data, Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder Questionnaire-7 (GAD-7), PTSD Symptom Checklist for DSM-5 (PCL-5), Pittsburgh Sleep Quality Questionnaire (PSQQ), Toronto Alexithymia Scale (TAS-26) and Quality of Life Scale edited by Prof. Chaban (CQLS). Statistical analysis includes descriptive statistics and Pearson correlation, which was carried out using SPSS Statistics 23.0 software. The study population consists (N=111, women (76.5%) and men (23.5%)). Strong, significant positive associations were found between all scale scores, including: PTSD, depression, anxiety, alexithymia, sleep and subjective quality disorders, latency, duration, daytime functioning disorders, and treatment (p > 0.001). In addition to treatment scores with anxiety, sleep latency, and duration (p>0.01). Strong negative correlations were found between the quality of life scores and other scores (p > 0.001), latency (p > 0.01), and sleep duration, and daytime functioning disorders and age (p > 0.05). Consequently, significant associations were found between higher rates of sleep disturbance and symptoms of PTSD, anxiety, depression, alexithymia, and poor quality of life.